ANALISIS SISTEM AKUNTANSI KLAIM KECELAKAAN DIRI (PERSONAL ACCIDENT) PADA PERUSAHAAN ASURANSI BUMIDA - Alam, Andi Syamsu; Triani, Neks; Chairunnas, Arnadi (Komunitas Manajemen Kompetitif, 2025)
This study aims to analyze the effectiveness of the personal accident claim accounting system at BUMIDA Insurance Company, focusing on the accuracy of claim recognition, the effectiveness of internal controls, and the system’s compliance with applicable accounting standards, particularly PSAK 62 and PSAK 74. A qualitative case study approach was employed, with data collected through in-depth interviews, field observations, and analysis of internal documentation. The findings indicate that delays in claim recognition and manual document verification are the main obstacles affecting the accuracy of financial reporting and increasing the risk of fraud. Furthermore, the current claim accounting system at BUMIDA has not fully aligned with PSAK 74, especially regarding the measurement of insurance liabilities and the separation of insurance components. Keywords: claim accounting system, personal accident, PSAK 117, internal control, BUMIDA insurance, digitalization